Comparative Study on the Treatment of Ankyloglossia by Using Er:YAG Laser or Traditional Scalpel. Issue 8 (6th November 2021) - Shang, Jiang; Han, Maoqiang; Sun, Jing; Xu, Dapeng; Qu, Weidong
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The aim of this study was to compare, respectively, postoperative pain, wound healing, and patient satisfaction following lingual frenum extension treated with the Erbium Yttrium aluminum garnet. (Er:YAG) laser or the conventional scalpel. Twenty-eight patients receiving lingual frenectomy were randomly assigned to the Er:YAG laser group (n = 15) or the traditional scalpel group (n = 13). The surgical parameters were set to 3W or 4W basing on types of the lingual frenum when the Er:YAG laser was working. The same procedure was applied to the traditional scalpel group with transverse incision and longitudinal suture. The postoperative pain, wound healing and patient satisfaction were evaluated at 3 hours, 3, 7, and 30 days after operation. The visual analog scale score of postoperative pain in Er:YAG laser group was lower than that in traditional scalpel group at each time point. The wound healing score of the laser group were significantly lower than that of the traditional scalpel group at 3 and 7 days after surgery. There was no significant difference in mental, diet, and language satisfaction between the 2 groups at different time points after operation. In conclusion, Er:YAG laser was superior to the scalpel regarding minor soft-tissue surgery, and it could relieve the pain and discomfort of patients in the early stage of wound.